2021
DOI: 10.3390/molecules26123651
|View full text |Cite
|
Sign up to set email alerts
|

Boswellic Acids Show In Vitro Activity against Leishmania donovani

Abstract: In continuation of our search for leads from medicinal plants against protozoal pathogens, we detected antileishmanial activity in polar fractions of a dichloromethane extract from Boswellia serrata resin. 11-keto-β-boswellic acid (KBA) could be isolated from these fractions and was tested in vitro against Leishmania donovani axenic amastigotes along with five further boswellic acid derivatives. 3-O-acetyl-11-keto-β-boswellic acid (AKBA) showed the strongest activity with an IC50 value of 0.88 µM against axeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This study has demonstrated, for the first time, fractions rich in secondary metabolites such as terpenes and their derivatives present in the leaves of M. alceifolia , which confer a possible in vitro action against the axenic amastigote and in silico action against some key proteases in the biosynthetic pathways of L. mexicana . However, studies have demonstrated that triterpene extracts and fractions obtained from Boswellia and Commiphora spp., particularly methyl Commate A (boswellic acids), exhibit activity against axenic amastigotes L. donovani [ 45 , 46 , 47 ]. β-Amyrin from Leuconotis eugenifolius inhibited L. donovani and extracts of species of the genus Eugenia ( E. uniflora and E. umbeliflora ) against L. amazonensis [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study has demonstrated, for the first time, fractions rich in secondary metabolites such as terpenes and their derivatives present in the leaves of M. alceifolia , which confer a possible in vitro action against the axenic amastigote and in silico action against some key proteases in the biosynthetic pathways of L. mexicana . However, studies have demonstrated that triterpene extracts and fractions obtained from Boswellia and Commiphora spp., particularly methyl Commate A (boswellic acids), exhibit activity against axenic amastigotes L. donovani [ 45 , 46 , 47 ]. β-Amyrin from Leuconotis eugenifolius inhibited L. donovani and extracts of species of the genus Eugenia ( E. uniflora and E. umbeliflora ) against L. amazonensis [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…To determine the anti-leishmanial (L. major) activity of any compound inhibitory (IC50), cytotoxic (CC50), and effective concentrations (EC50) are measured, similarly the anti-leishmanial activity of U. dioica extract from leaves was determined to suppressing promastigotes and amastigotes growth and the best concentrations were 3500 and 6000 μg/ml [25]. L. donovani axenic amastigotes IC50: 0.88 µM [26] Crude extracts and fractions…”
Section: Anti-leishmanial Compoundsmentioning
confidence: 99%
“…Quercetin-3,7-dimethylether L. donovani IC50: 4.5 ± 0. In other research studies [26] 3-O-acetyl-11-keto-β-boswellic acid (AKBA) is extracted from the Boswellia serrata resin which showed antileishmanial activity. The activity was seen against L. donovani.…”
Section: Stems Of Cuscuta Hyalinamentioning
confidence: 99%
See 1 more Smart Citation
“…Leishmaniasis causes 20,000–30,000 deaths worldwide every year. It is transmitted to humans through the bite of infected female sandflies (Greve et al., 2021). The disease has three forms: cutaneous leishmaniasis ( Leishmania major , Leishmania tropica , Leishmania mexicana , and Leishmania amazonensis ), which is the most common and causes skin lesions and scarring; mucocutaneous leishmaniasis ( Leishmania braziliensis ), which affects the nasal and oral mucosa and can extend to the oropharynx and larynx; and visceral leishmaniasis ( Leishmania donovani and Leishmania infantum / Leishmania chagasi ), the most severe form, also known as kala‐azar.…”
Section: Introductionmentioning
confidence: 99%